Optimasi Faktor Eksposi pada Pemeriksaan Radiografi Thorax menggunakan Computed Radiography - Sri Sugiarti; Surip Surip; Merrytiana Fadila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Concerning radiation safety must meet several radiation protection requirements which include justification or utilization of nuclear power, dose limitation, optimization of protection, and radiation safety. The purpose of this study was to determine the optimization of the exposure factor selection and determine the radiation dose received by the patient based on the selection of exposure factors on the thorax examination. The author observed the use of exposure factors on chest radiographic examination with a sample of 60 people. The design of this study uses the correlational method. The independent variables in this study are age, body weight, object thickness, kV, and mAs. Dependent variable exposure to radiation dose on chest examination. The conclusion of this study is the dose exposure level is influenced by age, object thickness, weight, and use of exposure factors which will then be obtained by the DRL (Diagnostic Reference Level) value.